Pengaruh Kepemilikan Institusional, Ukuran Dan Umur Perusahaan Terhadap Kinerja Intellectual Capital Industri Keuangan di BEI - Roviko, Ainun; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2018)
Evaluate performance intellectual capital of company is an important thing because this will contribute to the company competitive advantage in the future. This study aims to obtain empirical evidence of the impact institutional ownership, firm size and firmage on intellectual capital performance financial industry listed on Indonesian Stock Exchange 2015-2017.Intellectual capital performance measured by VAIC TM . This research used non- probability sampling technique with purposive sampling method and 37 company as a sample and 111 observation. Secondary data obtained from the annual financial report of the financial industry. The result of this research indicate that institutional ownership hasnot affecting the intellectual capital performance. The result of this search also indicate that firm size and firm age has a positive effect on intellectual capital performance. Keywords : Institutional ownership, size and firm age, financial industry, intellectual capital.